2020
DOI: 10.1186/s12893-020-00806-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidental hepatic tuberculosis during planned resection of locally advanced ampullary carcinoma: a case report

Abstract: Background: Tuberculosis (TB) is classified according to the site of disease as pulmonary or extrapulmonary. Extrapulmonary TB is less common than its counterpart in which it can be found anywhere in the body including the liver. Similar to ampullary carcinoma, TB liver can manifest with jaundice and deranged liver function tests, particularly in the obstructed biliary systems. Case presentation: A 43-year-old gentleman with locally advanced ampullary carcinoma was noticed to have multiple suspicious liver nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It continues to infect a vast segment of society every year with an estimated 10 million individuals contracting TB and 1.6 million eventually succumbing to the disease in 2017 [1] . In Malaysia, TB does not only cause morbidity on the pulmonary tuberculosis (PTB), but also on the extra-pulmonary type [2–4] . The sputum smear test is widely used to diagnose PTB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It continues to infect a vast segment of society every year with an estimated 10 million individuals contracting TB and 1.6 million eventually succumbing to the disease in 2017 [1] . In Malaysia, TB does not only cause morbidity on the pulmonary tuberculosis (PTB), but also on the extra-pulmonary type [2–4] . The sputum smear test is widely used to diagnose PTB.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In Malaysia, TB does not only cause morbidity on the pulmonary tuberculosis (PTB), but also on the extrapulmonary type. [2][3][4] The sputum smear test is widely used to diagnose PTB. PTB treatment targets include sputum smear conversion at the end of the intensive phase of anti-TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…TB is deemed endemic in Malaysia, with 29,000 new cases annually and an incidence rate of 92 cases per 100,000 population in 2018 6 . From this, there are a minority of cases that involved extrapulmonary TB, including gastrointestinal TB 7–9 . Hence, this report presents a rare case of a colo‐appendico‐duodenal fistula, which to the extent of the authors' knowledge, is the first case reported in our region.…”
Section: Introductionmentioning
confidence: 71%
“…The ileo-caecal junction is the most commonly affected area in abdominal tuberculosis, besides other hollow organs [1]. Solid organs such as the liver, spleen or kidneys occur more commonly than the pancreas [2]. Herein, we describe a case of disseminated tuberculosis involving the pancreas, mimicking a clinical presentation of advanced pancreatic carcinoma.…”
Section: Introductionmentioning
confidence: 93%